Integration of biommicry into science education - Çoban, Merve (My University, 2019)
Biomimicry is called “innovation inspired by nature." This study aims to integrate biomimicry into science education by proposing a teaching approach for primary school students. Action research approach as the qualitative research method was used. The developed “Biomimicry Teaching Approach” has been applied in a 5th grade classroom the researcher teaches in a public school in Gaziantep. According to this model, the students firstly were presented with different kinds of organisms in order to develop the ability to observe organisms and make relationship between structure and function. Secondly, they were introduced biomimicry with a variety of examples. Finally, the students were engaged with “Biomimicry Design Model”. At the end of the biomimicry lessons, the students designed their models through drawing and modeling inspired by a variety of organisms. The effects of “Biomimicry Teaching Approach” on student designs were analyzed. Results showed that 5th grade students mostly created their own design ideas inspired by the organisms which were presented throughout the biomimicry lessons. The students’ attempts to make different designs by taking inspiration from the organisms in nature and considering the function behind the physical structure of the organisms show that the students can produce creative and applicable design ideas inspired by nature when they are introduced biomimicry through “Biomimicry Teaching Approach."

Biyomimikri “doğadan ilham alan inovasyon” olarak tanımlanır. Bu çalışmada ilköğretim seviyesinde bir öğretim yaklaşımı sunularak biyomimikrinin fen eğitimine uyarlanması amaçlanmıştır. Çalışmada nitel araştırma yöntemlerinden eylem araştırması kullanılmıştır. Geliştirilen “Biyomimikri Öğretim Yaklaşımı”, araştırmacının Gaziantep'teki bir devlet okulunda dersine girdiği 5. Sınıf öğrencilerine uygulanmıştır. Bu modele göre, ilk olarak canlıları gözlemleme ve yapı ile fonksiyon arasında ilişki kurma becerisi geliştirmek amacıyla öğrencilere farklı türdeki canlılar sunulmuştur. İkinci olarak, “biyomimikri” öğrencilere çeşitli örnekleriyle tanıtılmıştır. Son olarak öğrenciler “Biyomimikri Tasarım Modeli” kapsamında öğrendiklerini uygulamışlardır. Bu tasarım modeli sonunda öğrenciler çeşitli canlılardan ilham alarak kendi tasarımlarını çizerek ve modelleyerek ortaya koymuşlardır. Çalışmada biyomimikri öğretim yaklaşımının öğrenci tasarımları üzerindeki etkileri analiz edilmiştir. Çalışmanın sonuçları 5. sınıf öğrencilerinin çoğunlukla biyomimikri derslerinde sunulan canlılardan ilham alarak kendi tasarım fikirlerini oluşturduklarını göstermiştir. Öğrencilerin doğadaki canlılardan esinlenerek ve canlıların fiziksel yapısının arkasındaki işlevi göz önünde bulundurarak farklı tasarımlar ortaya koymaya çalışmaları, öğrencilerin biyomimikriyi “Biyomimikri Öğretim Yaklaşımı” yoluyla öğrendiklerinde doğadan ilham alan yaratıcı ve uygulanabilir tasarım fikirleri üretebileceklerini göstermiştir.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2019
Keywords: Biyomimikri; Doğadan ilham alan tasarım; Biyomimikri öğretim yaklaşımı; Biyomimikri yasarım modeli; Fen bilimleri eğitimi; Biomimicry; Nature inspired design; Biomimicry teaching approach; Biomimicry design model; Science education